Biocompatibility characteristics of the metal organic framework ZIF-8 for therapeutical applications. (June 2018) - Hoop, Marcus; Walde, Claudio F.; Riccò, Raffaele; Mushtaq, Fajer; Terzopoulou, Anastasia; Chen, Xiang-Zhong; deMello, Andrew J.; Doonan, Christian J.; Falcaro, Paolo; Nelson, Bradley J.; Puigmartí-Luis, Josep; Pané, Salvador
Graphical abstract: Highlights: Biocompatible characteristics of zeolitic imidazole framework 8 (ZIF-8). Threshold concentration determines biocompatible characteristics. Zinc ions major source for limited biocompatibility due to enhanced ROS production. Concentrations above critical threshold cause severe DNA damage. ZIF-8 loaded with Insulin enables Diabetes therapy significantly below threshold. Abstract: Metal–organic frameworks (MOFs) are a class of crystalline materials constructed from organic linkers and inorganic nodes. MOFs typically possess ultra-high surface areas and pore volumes; thus, they are ideal candidates for biomedical applications. Zinc Imidazolate Framework 8 (ZIF-8) has been widely established in the literature as a potential candidate for on-demand drug delivery applications. Indeed, ZIF-8 has a remarkable loading capacity, stability in physiological environments, and tunable drug release properties. However, the use of ZIF-8 for in vivo applications requires a clear understanding of the interaction of ZIF-8 with biological tissue. In this work, we investigated the biocompatibility of ZIF-8 toward six different cell lines representing various body parts (kidney, skin, breast, blood, bones, and connective tissue). Our results suggest that ZIF-8 has no significant cytotoxicity up to a threshold value of 30 μg mL −1 . Above 30 μg mL −1, the cytotoxicity is shown to result from the influence of released Zinc ions (Zn 2+ ) on the mitochondrial ROS production. This adverse effect is responsible for cell cycle arrest in the G2/M phase due to irreversible DNA damage, ultimately initiating cellular apoptosis pathways. Due to this insight, we encapsulated a hormone, insulin, into ZIF-8 particles and then compared its drug delivery capabilities to the aforementioned cytotoxicity values. Our results suggest that ZIF-8 is suitable for therapeutic applications. Furthermore, this study establishes a clear understanding of the interaction of ZIF-8 and its constituents with various cell lines and highlights the important biocompatibility factors that must be considered for future in vivo testing.